Measuring Soil Electrical Conductivity to Delineate Zones of Variability in Production Fields - Gretchen Sassenrath; S. Kulesza (Kansas Agricultural Experiment Station Research Reports, 2017)
Production fields in southeast Kansas are highly variable. Differences in elevation and changes in soil texture contribute to unevenness in plant-available moisture and nutrients, resulting in significant inconsistencies in crop production and yield within a field. These variabilities complicate management and impact the return on investments from different areas of the field. Identification of the regions of variability is possible through several methods, including visual inspection, remote imagery, and yield maps. An additional method of assessing soil variability is by measuring the electrical conductivity of the soil. Measuring apparent electrical conductivity gives a map of the spatial distribution of soil properties, which can be used to identify potential limitations to production and develop site-specific management. Delineation of within-field variability can be used to target production inputs to better match potential crop yield with inputs to maximize return on investment.
Keywords: crops; soil variability; soil erosion; claypan; electrical conductivity; terrain analysis